2017
DOI: 10.1002/pd.5025
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of congenital cytomegalovirus infection in 115 cases: a 5 years' single center experience

Abstract: Optimal timing of amniocentesis in women with primary infection in early gestation should be reevaluated in a prospective study. Analysis of FB markers may be beneficial in the individual management of pregnant women with confirmed congenital CMV infection. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 40 publications
2
36
0
5
Order By: Relevance
“…In all four of these cases, maternofetal transmission was excluded at birth. A recent study confirmed that an earlier amniocentesis before 20 weeks can also reliably assess the risk of transmission; therefore, we believe that this limitation did not affect our results.…”
Section: Discussionmentioning
confidence: 52%
“…In all four of these cases, maternofetal transmission was excluded at birth. A recent study confirmed that an earlier amniocentesis before 20 weeks can also reliably assess the risk of transmission; therefore, we believe that this limitation did not affect our results.…”
Section: Discussionmentioning
confidence: 52%
“…In 338 cases, adequate specimen were available at termination of pregnancy or at birth for the diagnosis of congenital CMV infection (cCMV). Sixty‐three of the 338 pregnancies were part of our previous study . Time between seroconversion and invasive PD was estimated by patient's history and available laboratory results.…”
Section: Diagnostic Value Of CMV Dna Detection In Amniotic Fluid Betwmentioning
confidence: 99%
“…1,2 In a recent publication, we described a single centre experience on invasive PD in a 5-year cohort of 115 women with CMV primary infection. 3 In this study, we did not observe a significant difference in sensitivity whether AC was performed ≥17 + 0 or ≥20 + 0 WG, as long as the interval between seroconversion and invasive PD was >8 weeks. However, the number of cases with intrauterine transmission and AC before 21 WG was limited.…”
mentioning
confidence: 99%
“…This threshold was combined with a timeframe of at least 6 weeks between initial diagnosis of maternal HCMV infection and PCR testing . Enders and colleagues showed that if this timeframe was extended up to 8 weeks between seroconversion and AC, the overall sensitivity of PCR from AF taken after 17‐week gestation was comparable with that of 21 weeks …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Enders and colleagues showed that if this timeframe was extended up to 8 weeks between seroconversion and AC, the overall sensitivity of PCR from AF taken after 17-week gestation was comparable with that of 21 weeks. 13 Goegebuer et al described a correlation between AF-HCMV viral load (VL) and the GA at the time of AC, but no correlation between the copy numbers in AF and the fetal and neonatal outcomes was found. 14 In contrast, recent data of Leruez-Ville and colleagues implicate that high VL may be an independent prognostic factor for clinical outcome at birth.…”
Section: Introductionmentioning
confidence: 99%